colorimetric evaluation of Cercon zirconia and metal ceramic restorations in two thicknesses of veneering porcelain - Dorriz H; Memarian M; Madani A; Sedighpor L; Shamshiri AR (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: The aim of this study was to evaluate the effect of zirconia and base metal cores on the color of restorations. Furthermore, the effect of different backings on the color of cercon zirconia was evaluated."nMaterials and Methods: The specimens were Cercon zirconia and metal ceramic discs with "high Au" and "base metal" alloys. Cercon zirconia discs were veneered with veneering shade of A2 and two thickness of porcelain"n(0.7 mm, 1.2 mm). There were 3 discs in each group. Metal ceramic discs were made of "nickel-chromium" alloy (Verobond) and "high Au" alloy (World 89) and two shades (A2, A3.5) and two thicknesses of veneering porcelain. 3 types of backing (high Au, nickel-chromium and A3 shade composite) were made for Cercon zirconia discs. Spectrophotometric evaluation of zirconia discs (on 3 backings) and metal ceramic discs was done. One-way ANOVA and Tukey tests were used for data analysis."nResults: There were no significant differences between the amounts of L*, a*, b* for Cercon zirconia on different backings (P>0.05). In comparison between different core groups, a* was significantly higher in metal ceramic groups compared with that of zirconia groups (P<0.05)."nConclusion: Cercon zirconia can completely mask the underlying backing.